Evaluating the net effect of sulfadimidine on nitrogen removal in an aquatic microcosm environment. (May 2019) - Wang, Mei; Xiong, Wenguang; Zou, Yong; Lin, Manxia; Zhou, Qin; Xie, Xiying; Sun, Yongxue
Abstract: Antibiotics enter into aquatic pond sediments by wastewater and could make detrimental effects on microbial communities. In this study, we examined the effects of sulfadimidine on nitrogen removal when added to experimental pond sediments. We found that sulfadimidine increased the number of sulfadimidine resistant bacteria and significantly increased the abundance of sul2 at the end of the incubation time (ANOVA test at Tukey HSD, P < 0.05). In addition, sulfadimidine decreased the N2 O reduction rate as well as the amount of nitrate reduction. Pearson correlation analysis revealed that the N2 O reduction rate was significantly and negatively correlated with narG (r = −0.679, P < 0.05). In contrast, we found a significant positive correlation between the amount of nitrate reduction and the abundance of narG (r = 0.609, P < 0.05) and nirK (r = 0.611, P < 0.05). High-throughput sequencing demonstrated that Actinobacteria, Euryarchaeota, Gemmatimonadetes, Nitrospirae, Burkholderiaceae (a family of Proteobacteria ), and Thermoanaerobaculaceae (a family of Firmicutes ) decreased with sulfadimidine exposure. In sediments, Actinobacteria, Bacteroidetes, Cyanobacteria, Epsilonbacteraeota, Euryarchaeota, Firmicutes, Gemmatimonadetes, and Spirochaetes at may play key roles in nitrogen transformation. Overall, the study exhibited a net effect of antibiotic exposure regarding nitrogen removal in an aquatic microcosm environment through a combination of biochemical pathways and molecular pathways, and draws attention to controlling antibiotic pollution in aquatic ecosystems. Graphical abstract: Image 1 Highlights: Sulfadimidine decreased the N2 O reduction rate and the amount of nitrate reduction. Sulfadimidine increased resistant bacteria and the abundance of sul2. Proteobacteria, Acidobacteria and Chloroflexi were the most abundant in sediment. Burkholderiaceae and Thermoanaerobaculaceae decreased under sulfadimidine stress. No significant correlation between N2 O reduction and functional genes except narG.